2013
DOI: 10.1051/0004-6361/201219846
|View full text |Cite
|
Sign up to set email alerts
|

The long bar as seen by the VVV Survey

Abstract: Context. There is still some debate about the presence and the morphological properties of the long bar in the inner Galaxy. Aims. We investigate the morphological properties of the long Galactic bar using the VVV survey extending star counts at least 3 mag deeper than 2MASS. Our study covers the relatively unexplored negative longitudes of the Galactic bar. We obtain a detailed description of the spatial distribution of star counts towards the long Galactic bar as well as to measure its parameters. Methods. W… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 69 publications
2
15
0
Order By: Relevance
“…The position angle of this longer component has been constrained to ∼45 degrees in such studies (e.g. López-Corredoira et al, 2007;Cabrera-Lavers et al, 2007;Hammersley et al, 2000;Churchwell et al, 2009;Amôres et al, 2013). On the other hand, the recent model of the global distribution of red-clump stars from Wegg and Gerhard (2013) provided a precise measurement for the B/P Bulge position angle of 27 ± 2 degrees, in agreement with the studies done at larger distances from the Galactic plane.…”
Section: The Structure Of the Milky Way Bulgesupporting
confidence: 79%
“…The position angle of this longer component has been constrained to ∼45 degrees in such studies (e.g. López-Corredoira et al, 2007;Cabrera-Lavers et al, 2007;Hammersley et al, 2000;Churchwell et al, 2009;Amôres et al, 2013). On the other hand, the recent model of the global distribution of red-clump stars from Wegg and Gerhard (2013) provided a precise measurement for the B/P Bulge position angle of 27 ± 2 degrees, in agreement with the studies done at larger distances from the Galactic plane.…”
Section: The Structure Of the Milky Way Bulgesupporting
confidence: 79%
“…• -45 • ) and half-length (3.7 -4.4 kpc) (see Benjamin et al 2005;López-Corredoira et al 2007;CabreraLavers et al 2007CabreraLavers et al , 2008Vallenari, Ragaini, & Bertelli 2008;Churchwell et al 2009;Amôres et al 2013). Moreover, the vast majority of these studies favour the thesis for which the Milky Way hosts two bars: the main bar confined in the bulge within |l| ≤ 10…”
Section: Zoccali and Valentimentioning
confidence: 99%
“…The black dotted circles indicate the heliocentric distance, while the green dashed circles indicate the galactocentric radius. The long bar as from Amores et al (2013) is shown in gray, and the black rectangles indicate the sources considered at the edges of the bar in the present paper. The Sun is at the bottom of the image (orange circle) and the GC is represented by the black cross at the position (0,0).…”
Section: Candidate Protostellar Clump Selection Criteriamentioning
confidence: 99%
“…According to the information about the MW structure currently available, mostly based on spectroscopic observations of the ISM and star counts (see, for example Benjamin et al (2005); Rodriguez-Fernandez & Combes (2008)), the MW is a barred spiral Galaxy with two main arms and several secondary arms. The long in-plane Galactic bar (Lopez-Corredoira et al 2001;Benjamin et al 2005;López-Corredoira et al 2007;Amores et al 2013) has length, horizontal and vertical thickness of approximately 7.8 kpc × 1.2 kpc × 0.2 kpc, respectively. The major axis is inclined by an angle of approximatley 42…”
Section: Introductionmentioning
confidence: 99%